Sense of Security and Production of Place in Gated Communities: Case-studies in Lagos, Nigeria - Adetokunbo, Ilesanmi (International Journal of Property Sciences (E-ISSN: 2229-8568), 2013)
The emergence of Gated Communities (GCs) represents one of the most intriguing phenomena and a crucial debate in an urbanizing globe. This study explored the link between sense of security and the negotiation of place by examining the potentials for place production in gated communities (GCs). Although a dearth of comprehensive data presently exists on GCs in Lagos, their increasing emergence is apparent. This research adopted a case-study approach, collecting primary data through field observations and qualitative in-depth interviews with eighteen (18) residents of four (4) purposively selected gated estates out of twenty (20) estates identified from preliminary mapping exercises. The qualitative data were subjected to content analysis and comparative evaluation. Findings reveal that characteristics that suggest the potential for place production vary according to the evolution and types of the gated developments. The medium-income gated estates originally built as public housing evidenced greater sense of security and place prospects than the private gated estates for the more affluent. The study concluded that the security-driven motive of gated communities could be a dominant factor in the negotiation of place, thus reinforcing the possible link between sense of security and production of place in gated communities.